Detection of latent tuberculosis infection in BCG vaccinated children - Paluch-Oleś, Jolanta; Magryś, Agnieszka; Kozioł-Montewka, Maria (Polish Journal of Public Health, 2011)
Introduction. Children with tuberculosis represent about 11% of all notified incidences of the disease. Especially young children are at high risk of infection because of the decreased ability of their immunes to combat the pathogens and children <5 years of age are the most vulnerable. In Poland tuberculin skin test has been used as Latent Tuberculosis Infection (LTBI) detection method since 1966. Because of the low specificity of TST, the global actions were undertaken aimed at introducing to use more specific test for LTBI detection. Recently, QuantiFERON-TB Gold In-Tube assay has been used as an alternative to TST for the diagnosis of LTBI. There are only few reports about the precision of the assay in pediatric cases. Aim. The purpose of the study was to assess LTBI rate in children as well as to determine usefulness of QFT-IT assay for LTBI detection in BCG vaccinated children. Material and Methods. One hundred fifty six patients aged 0-18 years were enrolled into the study. The children were selected due to suspected active tuberculosis (pulmonary or extrapulmonary) or because of the considered treatment with TNF inhibitors. The presence of LTBI was assessed by medical history and screening tests: chest radiography and QFT-IT. The evaluation of the medical history included: current symptoms, prior history of treatment for tuberculosis and close contact with active pulmonary tuberculosis within the last year. Results. Eight children (5.1%) had positive QFT-IT results. The percentage of children with positive QFT-IT results was the highest in the age group >3≤12. In the analyzed group of patients, 127 (81.4%) had negative tests results. Among these, one QFT-IT result was subliminal (0.31UI/ml). Twenty one (13.5%) of the 156 studied children had indeterminate QFT-IT results. The proportion of indeterminate results was the highest in the youngest age group. Conclusions. Our results indicate the low rate of LTBI among the studied children. The infection rate detected with QFT-IT is more likely than identifying with TST owing to small rate of childhood TB in Poland.